KELAYAKAN INDUSTRI KERUPUK JAMUR TIRAM DI KABUPATEN BOGOR - Purwoko dan Yandra Arkeman (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTOyster mushroom can be processed into various cooking and snack, such as crisps, pikel, and crispy. Oyster mushroom chips are uncommon and brand new secondary product. Nowadays oyster mushroom chips still have not found in Bogor yet. The analysis of market and marketing showed that the production of chips in Indonesia was still under the limit of production and appropriate to produce in the future. It was showed from the utility rate, which was still under 100%. Cisarua Bogor is the optimum location to develop the chips factory and need 29 employees. This industry required investment Rp 386.886.813,00 consist of working capital and fix capital. Pay back period during 1.7 years. Net present value is Rp 357.960.700,00, internal rate of return is 37 % and net benefit-cost ratio is 1.9. This means that project is feasible to be applied. Based on the sensitivity analysis for the decreasing selling price until 15 % and sensitivity analysis for the increasing raw material price until 20 %.